Frequency of Delayed Healing of Extraction Socket in Diabetic Patients with Different Glycemic Control - Murtaza,; Dad, Fazal; Uppal, Asma; Bilal, Muhammad; Abdullah, (Indus Journal of Bioscience Research, 2025)
Background: Impaired angiogenesis, weakened immune systems, and decreased collagen synthesis make delayed healing of extraction sockets in diabetic patients a prevalent clinical problem. The way diabetics manage their blood sugar levels has a big impact on how well oral surgery goes for them. Knowledge of the connection between blood glucose levels and healing can help inform postoperative care plans and clinical judgement. Objective: The objective of this study is to figure out how common delayed healing is in extraction sockets in diabetic patients and investigating the relationship between delayed healing and glycaemic control levels (good, moderate, and poor). Identifying important clinical and demographic factors that may affect wound healing results, such as gender, age, and the length of diabetes, is another goal. Methodology: A cross-sectional study was carried out at a Quetta tertiary care hospital, using random sampling to choose a sample of 120 diabetic patients. Based on their HbA1c levels, participants were divided into three glycaemic control groups: good (<7%), intermediate (7–8.9%), and poor (≥9%). Over a 21-day period, follow-up assessments evaluated the patient's healing state. SPSS was used to analyze the data. Findings: Patients with good glycaemic control experienced delayed healing in 13.3% of cases, those with intermediate control in 32.5%, and those with poor control in 61.3%. Glycaemic levels and delayed healing were statistically significantly correlated. Furthermore, patients with diabetes for more than ten years and those older than fifty had higher rates of delayed socket healing. Conclusion: The results show a clear link between delayed socket healing following dental extraction and inadequate glycaemic control. Post-extraction problems were more common in patients with higher HbA1c levels, highlighting the significance of strict glycaemic control in surgical preparation. These findings highlight the necessity of improved postoperative monitoring and preoperative glycaemic control in diabetic patients having oral surgery.